2017
DOI: 10.5144/0256-4947.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella sativa supplementation on lung function and inflammatory mediators in partly controlled asthma: a randomized controlled trial

Abstract: BACKGROUNDNigella sativa and its derivatives have been reported to have anti-inflammatory and bronchodilator effects, but the effects have been evaluated in only a few clinical studies.OBJECTIVESTo determine the effect of N sativa supplementation on inflammation of the airways and limitation of airflow in partly controlled asthma patients.DESIGNSingle-blind, placebo-controlled, randomized study.SETTINGAsthma and allergy clinic of a university hospital in eastern Saudi Arabia.PATIENTS AND METHODSPatients were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 40 publications
1
61
1
2
Order By: Relevance
“…14 Clinical study conducted by Salem et al reported that there was significant increase in the serum IFN-g and improvement in the ACT score after 12 weeks of Nigella sativa supplementation in asthmatic patients. 18 This study showed that NSO treatment increase of IFN-g and decrease of IL-4 serum level. It indicates that there was stimulatory effect on Th1 cells and inhibitory effect on Th2 cells.…”
Section: Discussionmentioning
confidence: 87%
“…14 Clinical study conducted by Salem et al reported that there was significant increase in the serum IFN-g and improvement in the ACT score after 12 weeks of Nigella sativa supplementation in asthmatic patients. 18 This study showed that NSO treatment increase of IFN-g and decrease of IL-4 serum level. It indicates that there was stimulatory effect on Th1 cells and inhibitory effect on Th2 cells.…”
Section: Discussionmentioning
confidence: 87%
“…Three hundred and fifteen potentially relevant articles are identified initially. Finally, four RCTs are included in the meta-analysis [20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Screening Eligibility Included Figure 1. Flow diagram of the study search and selection process ies have found that Nigella sativa was well tolerated, and only mild and self-limited side effects were reported [21,22]. Several limitations exist in this meta-analysis.…”
Section: Records Excluded (N = 221)mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have reported differences in total antioxidant capacity changes of 0.09 ± 0.10 mmol/L [12], and forced expiratory volume in 1 s (FEV1), FEV25-75%, peak expiratory flow variability, and fractional expired nitric oxide (FeNO) values of 7.70 ± 8.50%, 0.40 ± 0.45 L/s, 5.80 ± 6.30, and 4.60 ± 5.00 ppb, respectively, after control or test food intake [13]. Hence, the sample size per arm for the proposed study was calculated as 20 (60 in total), based on a power of 80% and an α = 0.05 level of significance.…”
Section: Assumptionsmentioning
confidence: 99%